In Vitro Anti-Cancer Alkaloid and Flavonoid Extracted from the Erythrina variegata (Leguminoseae) Plant - Tati Herlina; Unang Supratman; Anas Subarnas; Supriyatna Sutardjo; Suseno Amien; Hideo Hayashi (Indonesian Society for Cancer Chemoprevention, 2011)
Erythrina plants, locally known as “dadap ayam”, are higher plant species and have been used as a folk medicine for treatment of cancer. To prove the effectiveness of the leaves and stem bark of E. variegata as an anti-cancer agent, the assay in this research was focused on in vitro test towards breast cancer cell T47D. In the course of our continuing search for novel anti-cancer agent from Erythrina plants, the methanol extract of the leaves and stem bark of E. variegata showed significant anti-cancer activity against breast cancer cell T47D in vitro using the Sulphorhodamine B (SRB) assay. By using the anti-cancer activity to follow the separations, the methanol extract was separated by combination of column chromatography. The chemical structure of an anti-cancer compounds were determined on the basis of spectroscopic evidence and comparison with the previously reported and identified as an erythrina alkaloid (1) and isoflavonoid (2). Compounds (1-2) showed anti-cancer activity against breast cancer cell T47D used with IC50 of 1.0 and 3.3 µg/mL, respectively. This results strongly suggested that E. variegata is promising sources for anti-cancer agents. Keywords: Anti-cancer, Erythrina variegata, Leguminoseae